Profile And Risk Factors of Stevens Johnson Syndrome–Toxic Epidermal Necrolysis on Adult Patients in Dr. Moewardi General Hospital Surakarta from January 2019 – December 2022 - Putri, Osdatilla Esa; Oktavriana, Triasari; Octarica, Stella Gracia; Anandita, Benedikta Lauda; Pradestine, Sesia; Oktaviani, Trya (Health and Medical Journal, 2024)
Background: Steven Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are acute and life-threatening skin diseases, commonly induced by medications. Study on SJS/TEN in Indonesia was still limited, hence knowledge about the profile and risk factors of SJS/TEN patients is still required to provide appropriate management and reduce patient mortality rate. This study aimed to determine the profile and risk factors of adult SJS/TEN patients in the inpatient installation of RSDM Surakarta. Methods: We conducted a cross sectional study using secondary data from medical records of SJS/TEN patients at the inpatient installation of Dr. Moewardi hospital, Surakarta from 2019 – 2022. Correlation tests on characteristics, comorbidity with length of stay (LoS) and discharge status were analyzed. Results: Of the total 147,531 inpatients, 35 (0.02%) of them were diagnosed with SJS/TEN, dominated by females (57.14%) with the mean  of 45.74 years old.  Most subjects were diagnosed with SJS (48.57%), followed by SJS/TEN (40.0%) and TEN (11.43%). The mean LoS was  ± 8 days. Most subjects were discharged alive (85.71%). Paracetamol was the most common causative drug (25.71%), followed by cefadroxil (11.43%). Acute kidney injury (AKI) was the most common comorbidity (14.29%, p = 0.040). Spearman Rank test obtained no correlation between comorbidities and LoS (r = 0.028 ; p = 0.842) as well as discharge status (r = 0.063 ; p = 0.651). Conclusion: SJS/TEN is rare case with high mortality rate. Patients’ comorbidities have a very weak correlation with LoS and discharge status. Initial knowledge of the patient’s profile and risk factors including comorbidity and causative drugs can optimise comprehensive therapy for SJS/TEN patients.